Clinical Profile of Peripartum Hysterectomy: A Cross-Sectional Study - Chaudahry, Amar Nath; Baral, Gehanath; Subedi, Shanti; Shah, Rajan (Journal of Nobel Medical College, 2026)
Background: An emergency obstetric treatment called a peripartum hysterectomy is used to treat potentially fatal bleeding or uterine rupture during or after childbirth. The aim of the study was to find the clinical profile, indications, and outcomes of emergency peripartum hysterectomy at a tertiary care hospital in eastern Nepal.Materials and Methods: A hospital-based cross-sectional study was conducted in the department of Obstetrics and Gynaecology, Nobel Medical College and Teaching Hospital, Biratnagar, from September 2022 to October 2023. All women who underwent peripartum hysterectomy were included. Demographic characteristics, obstetric history, indications, intraoperative findings, and postoperative outcomes were analyzed using descriptive statistics.Results: Among 7,974 deliveries, 31 underwent peripartum hysterectomy, giving an incidence of 3.88 per 1,000 deliveries. The mean maternal age was 29.7 ± 5.4 years, and most patients were multigravida (48.3% gravida 3). The leading indications were placenta accreta spectrum (25.8%), placenta previa (25.8%), postpartum hemorrhage (16.1%), and uterine rupture (12.9%). Hysterectomy followed cesarean delivery in 74% of cases. All patients required blood transfusion, 51.6% required ICU admission, and 19.3% sustained bladder injury.Conclusion: Abnormal placentation and previous cesarean sections are the major contributors. Early antenatal identification of high-risk cases and multidisciplinary “accreta team” management may help prevent emergency hysterectomy and improve maternal outcomes.